2018
DOI: 10.1128/aem.02164-17
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence and Genetic Diversity of Large phiCD211 (phiCDIF1296T)-Like Prophages in Clostridioides difficile

Abstract: (formerly ) is a pathogenic bacterium displaying great genetic diversity. A significant proportion of this diversity is due to the presence of integrated prophages. Here, we provide an in-depth analysis of phiCD211, also known as phiCDIF1296T, the largest phage identified in so far, with a genome of 131 kbp. It shares morphological and genomic similarity with other large siphophages, like phage 949, infecting , and phage c-st, infecting A PhageTerm analysis indicated the presence of 378-bp direct terminal repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 62 publications
0
36
0
Order By: Relevance
“…The vast majority of known CRSIPR-Cas systems are encoded by cellular organisms and deployed to counter the replication of MGE, but some MGE also carry functional CRISPR-Cas systems. For instance, CRISPR-Cas systems and stand-alone CRISPR arrays have been identified in a number of prophages (Hargreaves et al, 2014;Chénard et al, 2016;Zheng et al, 2016;Garneau et al, 2018) and in the case of a Vibrio-infecting bacteriophage have been shown to target for destruction a pathogenicity island integrated in the host genome (Seed et al, 2013). By contrast, a subgroup of Tn7-like transposons has been hypothesized to employ the encoded CRISPR-Cas system for CRISPR-guided transposition (Peters et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of known CRSIPR-Cas systems are encoded by cellular organisms and deployed to counter the replication of MGE, but some MGE also carry functional CRISPR-Cas systems. For instance, CRISPR-Cas systems and stand-alone CRISPR arrays have been identified in a number of prophages (Hargreaves et al, 2014;Chénard et al, 2016;Zheng et al, 2016;Garneau et al, 2018) and in the case of a Vibrio-infecting bacteriophage have been shown to target for destruction a pathogenicity island integrated in the host genome (Seed et al, 2013). By contrast, a subgroup of Tn7-like transposons has been hypothesized to employ the encoded CRISPR-Cas system for CRISPR-guided transposition (Peters et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Over 1,300 C. difficile genomes have been fully sequenced and are available in public repositories, but thousands of additional genomes have also been sequenced and are available through collaborative research ( Garneau et al, 2018 ). Although uncommon, as many as 5–6 different prophages were identified in a single C. difficile genome ( Amy et al, 2018 ; Ramírez-Vargas et al, 2018 ).…”
Section: High Prevalence Of Prophages In C Difficile mentioning
confidence: 99%
“…However, between 1 and 3 prophages are more frequently observed, in addition to genomic “islands” containing phage-related genes. Recent studies highlighted the prevalence of large phage genomes that reside as extrachromosomal DNA in C. difficile ( Garneau et al, 2018 ; Ramírez-Vargas et al, 2018 ). For example, the large phiCD211/phiCDIF1297T and related phages, with genomes of ≥131-kb, have been detected in 5% of 2,584 C. difficile genomes analyzed, spanning 21 different multi-locus sequence types (MLST) ( Wittmann et al, 2015 ; Garneau et al, 2018 ).…”
Section: High Prevalence Of Prophages In C Difficile mentioning
confidence: 99%
See 2 more Smart Citations